Regulating Charge and Exciton Distribution in High-Performance Hybrid White Organic Light-Emitting Diodes with n-Type Interlayer Switch - Luo, Dongxiang; Yang, Yanfeng; Xiao, Ye; Zhao, Yu; Yang, Yibin; Liu, Baiquan (Nano-Micro Letters, 2017)
The interlayer (IL) plays a vital role in hybrid white organic light-emitting diodes (WOLEDs); however, only a negligible amount of attention has been given to n-type ILs. Herein, the n-type IL, for the first time, has been demonstrated to achieve a high efficiency, high color rendering index (CRI), and low voltage trade-off. The device exhibits a maximum total efficiency of 41.5 lm W−1, the highest among hybrid WOLEDs with n-type ILs. In addition, high CRIs (80–88) at practical luminances (≥1000 cd m−2) have been obtained, satisfying the demand for indoor lighting. Remarkably, a CRI of 88 is the highest among hybrid WOLEDs. Moreover, the device exhibits low voltages, with a turn-on voltage of only 2.5 V (>1 cd m−2), which is the lowest among hybrid WOLEDs. The intrinsic working mechanism of the device has also been explored; in particular, the role of n-type ILs in regulating the distribution of charges and excitons has been unveiled. The findings demonstrate that the introduction of n-type ILs is effective in developing high-performance hybrid WOLEDs. Highlights: 1 The n-type interlayer was demonstrated to achieve a high efficiency, high color rendering index (CRI), and low voltage trade-off. The device exhibits a maximum total efficiency of 41.5 lm W−1 and a low turn-on voltage of 2.5 V (>1 cd m−2). 2 High CRIs (80–88) at practical luminances (≥1000 cd m−2) were obtained, with a CRI of 88 being the highest among hybrid WOLEDs.